The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s10059-010-0084-1
|View full text |Cite
|
Sign up to set email alerts
|

OsCIPK31, a CBL-Interacting Protein Kinase Is Involved in Germination and Seedling Growth under Abiotic Stress Conditions in Rice Plants

Abstract: Calcineurin B-like protein-interacting protein kinases (CIPKs) are a group of typical Ser/Thr protein kinases that mediate calcium signals. Extensive studies using Arabidopsis plants have demonstrated that many calcium signatures that activate CIPKs originate from abiotic stresses. However, there are few reports on the functional demonstration of CIPKs in other plants, especially in grasses. In this study, we used a loss-of-function mutation to characterize the function of the rice CIPK gene OsCIPK31. Exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 41 publications
0
59
0
2
Order By: Relevance
“…Moreover, lately, five novel CIPKs and two CBLs have been discovered in kidney bean (Phaseolus vulgaris) and 43 putative CIPK genes that are closely related to rice CIPKs have been identified in maize (Zea mays; Hamada et al, 2009;Chen et al, 2011). A function of a rice CIPK has been reported for OsCIPK31, which was found to modulate responses to abiotic stresses during seed germination and seedling growth (Piao et al, 2010), and OsCIPK23, which turned out to be a multistress-induced gene likely regulating signaling pathways during pollination and drought stress responses (Yang et al, 2008). Another example for a multifunctional rice CIPK is OsCIPK15, which has been implicated in mediating oxygen deficiency tolerance as well as being involved in various PAMPinduced immune responses together with OsCIPK14 (Lee et al, 2009a;Kurusu et al, 2010).…”
Section: The Cbl-cipk Network Is Conserved In Many Plant Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, lately, five novel CIPKs and two CBLs have been discovered in kidney bean (Phaseolus vulgaris) and 43 putative CIPK genes that are closely related to rice CIPKs have been identified in maize (Zea mays; Hamada et al, 2009;Chen et al, 2011). A function of a rice CIPK has been reported for OsCIPK31, which was found to modulate responses to abiotic stresses during seed germination and seedling growth (Piao et al, 2010), and OsCIPK23, which turned out to be a multistress-induced gene likely regulating signaling pathways during pollination and drought stress responses (Yang et al, 2008). Another example for a multifunctional rice CIPK is OsCIPK15, which has been implicated in mediating oxygen deficiency tolerance as well as being involved in various PAMPinduced immune responses together with OsCIPK14 (Lee et al, 2009a;Kurusu et al, 2010).…”
Section: The Cbl-cipk Network Is Conserved In Many Plant Speciesmentioning
confidence: 99%
“…The diverse spectrum of plants in which CBL and CIPK function was analyzed encompasses species such as rice, rape (Brassica napus), wheat (Triticum aestivum), sorghum (Sorghum bicolor), apple (Malus domestica), cotton (Gossypium hirsutum), and poplar (Populus spp. ; Yang et al, 2008;Piao et al, 2010;Zhang et al, 2011Zhang et al, , 2013Chen et al, 2012;Wang et al, 2012;Deng et al, 2013;He et al, 2013). Moreover, lately, five novel CIPKs and two CBLs have been discovered in kidney bean (Phaseolus vulgaris) and 43 putative CIPK genes that are closely related to rice CIPKs have been identified in maize (Zea mays; Hamada et al, 2009;Chen et al, 2011).…”
Section: The Cbl-cipk Network Is Conserved In Many Plant Speciesmentioning
confidence: 99%
“…Conservation of the SOS pathway has been reported in rice, Brassica juncea , maize, tomato, Populus trichocarpa , Populus euphratica , and apple (Martínez-Atienza et al 2007 ;Wang et al 2007Wang et al , 2012aKumar et al 2009 ;Zhao et al 2009 ;Kushwaha et al 2011 ;Hu et al 2012 ;Tang et al 2010 ;Lv et al 2014 ;Oh et al 2008 ). From monocots like rice and wheat, using reverse functional genetic tool such as gain/loss of function of OsCIPK3, OsCIPK12, OsCIPK15, OsCIPK23, OsCIPK31, and TaCIPK14 has been demonstrated to be intricately involved in diverse abiotic stress pathways, namely, cold, salt, PEG, ABA, ethylene, and H 2 O 2 (Xiang et al 2007 ;Yang et al 2008 ;Piao et al 2010 ;Deng et al 2013a ). With more studies being reported from multiple plant species, the nitty-gritty of Ca 2+ signaling network and role of CDPK and CBL-CIPK proteins will be further elucidated.…”
Section: Oscbl8mentioning
confidence: 96%
“…Besides this, CIPK14 appeared to be regulated by both the circadian clock and PhyA, and involved in phytochrome A-mediated far-red light inhibition of greening in Arabidopsis seedlings [6]. In rice, OsCIPK31 has been identified to modulate responses to abiotic stresses during seed germination and seedling growth [5].…”
Section: Seedling Developmentmentioning
confidence: 98%